Simultaneous microfluidic spinning of multiple strands of submicron fiber for the production of free-standing porous membranes for biological application - Park, Do Yeun; Park, Jisoo; Jang, Heeyeong; Cheng, Jie; Kim, Soo Hyun; Lee, Sang-Hoon (IOP PUBLISHING LTD, 2017)
Microfibers produced using electrospinning and microfluidics-based technologies have been developed as a powerful tool in tissue engineering applications such as drug delivery and scaffolds. The applications of these fibers, however, have been limited because of the hazardous solvents used to make them, difficulties in controlling the pore sizes of their membrane forms, and downscaling the size of the fiber. Nevertheless, extending the use of these fibers, for example in the production of a freestanding porous membrane appropriate for cell-based research, is highly needed for tissue engineering, organ-on-a-chip, and drug delivery research and applications. Here, we fabricated a freestanding porous membrane by using a novel method that involved simultaneously spinning multiple strands of submicron-thick 'noodle-like' fibers. In addition to the novelty of the single noodle fiber in overcoming the size-reducing limitations of conventional microfluidic spinning methods, these fibers can hence form the units of 'noodle membranes' whose pores have sizes that the convention electrospinning method cannot achieve. We confirmed the potential of the noodle membrane to serve as a free-standing porous membrane in two simple experiments. Also, we found that noodle membranes have an advantage in loading different amounts of different materials in itself that it was also shown to be of use as a new type of scaffold for complex tissue regeneration. Therefore, the proposed noodle membrane can be an effective tool in tissue engineering applications and biological studies.
Keywords: TISSUE-ENGINEERING APPLICATIONS; SOLID-STATE NANOPORE; ALGINATE FIBERS; CHIP; FABRICATION; DEVICE; REGENERATION; GENERATION; SCAFFOLDS; COLLAGEN